Acute Myopericarditis in an Adolescent Mimicking Acute Myocardial Infarction. Issue 6 (June 2015) - Sharma, Jayendra; Fernandes, Nithi; Alvarez, Dora; Khanna, Shefali
<x xml:space="preserve">Abstract</x> Abstract Acute myopericarditis is primarily a pericarditic syndrome with variable myocardial involvement, as evidenced by elevated cardiac enzymes. It is a rare entity, exclusively seen in male adolescents and accounts for less than 2% of the cases of inpatient admissions for chest pain/pericarditis in the pediatric age group. The electrocardiographic changes of pericarditis include J point/ST segment elevation, which needs to be differentiated from the benign early repolarization pattern that is common in young adolescents and the subtle anterior ST segment elevation myocardial infarction. Differentiating acute myopericarditis from acute coronary syndromes can be challenging because they share the presenting triad of acute chest pain, ST segment changes, and elevated cardiac enzymes. The accurate distinction of myopericarditis from acute myocarditis or acute coronary syndrome is important because of their differences in risk for specific complications, prognosis, and treatment implications. We present a case of acute myopericarditis in an adolescent who presented with atypical precordial chest pain, accompanied by inferolateral focal electrocardiographic changes and significant elevation of cardiac enzymes. The differential diagnosis and management of myopericarditis is reviewed with a focus on electrocardiographic changes and troponin assays.